(untitled) - Miyakawa, Masuji (New York, 1907)
"West is west and east is east, never the twain shall meet"; Oh, what a remarkable specimen of self-conceited and egotistic epigram! If the words of Kipling and other eminent writers of his rank continued to play on the passions of the American populace, where would be landed the millions of diligent students of modern applied sciences, of arts, of Bible, of pedagogue, of humanity, and of civilization? West shall be east and East shall be west, and both must stand till the end of earth and sky, side by side "at God's great judgment seat!"
Keywords: Nhật Bản,Japan; Quan hệ đối ngoại,Foreign relations; Hoa Kỳ,United States